2013
DOI: 10.1148/radiol.13121101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Kinetic Properties of Background Parenchymal Enhancement throughout the Phases of the Menstrual Cycle

Abstract: Purpose:To develop and apply a semiautomatic method of segmenting fibroglandular tissue to quantify magnetic resonance (MR) imaging contrast material-enhancement kinetics of breast background parenchyma (BP) and lesions throughout the phases of the menstrual cycle in women with benign and malignant lesions. Materials and Methods:The institutional review board approved this retrospective HIPAA-compliant study, and informed consent was waived. From December 2008 to August 2011, 58 premenopausal women who had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…younger women) (1517). This is consistent with previous results with high temporal resolution imaging from Jansen et al (9), who sampled a limited number of slices with 7 second resolution and demonstrated that this approach detects significant differences between the early enhancement of DCIS and normal parenchyma, thus improving conspicuity of small diffuse cancers.…”
Section: Discussionmentioning
confidence: 99%
“…younger women) (1517). This is consistent with previous results with high temporal resolution imaging from Jansen et al (9), who sampled a limited number of slices with 7 second resolution and demonstrated that this approach detects significant differences between the early enhancement of DCIS and normal parenchyma, thus improving conspicuity of small diffuse cancers.…”
Section: Discussionmentioning
confidence: 99%
“…57 Wu et al 60 used a validated fully automated method that allowed segmentation and quantitative measure of fibroglandular tissues and BPE. 60 Qualitative and quantitative background parenchymal enhancement assessment Among the 11 studies that assessed BPE in both qualitative and quantitative methods, 7,20,22,24,29,30,32,34,35,46,47 27% (3/11) studies were published in 2015 (January-October 2015) and 73% (8/11) studies were published during 2010-2014. Most of the studies were performed in the USA (3/11 studies) and the Korea (3/11 studies).…”
Section: Quantitative Background Parenchymal Enhancement Assessmentmentioning
confidence: 99%
“…In a total of 14 studies, the authors stated the menstrual period. 7,20,22,24,25,27,30,31,39,45,46,55,56,60 In 8 of these 14 studies, breast MRI were performed ideally in the second week of the menstrual cycle. 7,22,24,25,27,45,56,60 In three studies, 37,47,58 the patients were post-menopausal females.…”
Section: Quantitative Background Parenchymal Enhancement Assessmentmentioning
confidence: 99%
“…Several studies have suggested that BPE represents physiological hormonal enhancement, reflecting hormone-related changes in breast composition and vascularity. Fluctuations in BPE have been demonstrated throughout the menstrual cycle, with the highest levels of enhancement in the second half of the menstrual cycle during the luteal phase when breast cell proliferation is at its highest [20]. BPE has also been demonstrated to reflect variations in estrogen-mediated vascular permeability, with increased BPE seen in women taking estrogen replacement therapy, and decreased BPE with anti-estrogen medications and in postmenopausal patients [2330].…”
Section: Disscussionmentioning
confidence: 99%